Disruption of Dictyostelium discoideum morphogenesis by overproduction of cAMP phosphodiesterase. - Faure, M (1988)
The development and cellular differentiation of Dictyostelium discoideum are disrupted in transformants secreting high levels of the cyclic nucleotide phosphodiesterase. The aggregation of these cells in the early stage of development proceeds rapidly and without the formation of organized streams. The later stages of development, in which differentiation into stalk and spore cells normally takes place, are completely blocked so that the transformants remain in spherical clusters of undifferentiated cells that do not elaborate the tip structure that regulates morphogenesis. These effects are due to overproduction of extracellular phosphodiesterase and demonstrate the role of cAMP during the aggregation phase of development as well as in the control of differentiation and pattern formation.